2017
DOI: 10.1155/2017/6010721
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and Prognostic Role of Long Noncoding RNA Linc00152 in Various Human Neoplasms: Evidence from Meta-Analysis

Abstract: Recent researches have demonstrated that long noncoding RNA linc00152 was aberrantly upregulated in multiple tumor types. High expression of linc00152 was associated with poor outcomes in cancer patients. Therefore, we conducted this meta-analysis to evaluate its potential value as a prognostic predictor in various human neoplasms. Eligible studies were searched through several electronic databases including PubMed, Embase, Web of Science, and the Cochrane Library. Eight original studies including 752 cancer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Most importantly, only STAiR18 showed a global overexpression in various cancer types [8]. This observation has since been confirmed by further publications [11][12][13]. Therefore, our preliminary data supported the view that STAiR18 contributes to STAT3-dependent tumorigenesis in multiple myeloma as well as in other cancer entities [8].…”
Section: Introductionsupporting
confidence: 87%
“…Most importantly, only STAiR18 showed a global overexpression in various cancer types [8]. This observation has since been confirmed by further publications [11][12][13]. Therefore, our preliminary data supported the view that STAiR18 contributes to STAT3-dependent tumorigenesis in multiple myeloma as well as in other cancer entities [8].…”
Section: Introductionsupporting
confidence: 87%
“…66,67 A metaanalysis of eight trials unveiled strong correlations between linc00152 and the diagnosis, prognosis, and metastasis of cancers, particularly lymph node metastases. 68 A recent metaanalysis of the data for 913 cancer patients further confirmed the diagnostic utility of linc00152 as well as its association with lymph node metastases, advances in the TNM stage, and shorter overall survival. 69 Because many studies have revealed the mechanisms underlying linc00152 effects in diverse cancers (Table 1), linc00152 or the molecules associated with its activities represent candidate therapeutic targets.…”
Section: Linc00152 Expression May Be Useful For Diagnosing and Predmentioning
confidence: 89%
“…Several meta‐analyses have verified the application of linc0012 as a biomarker for diagnosing cancers . A meta‐analysis of eight trials unveiled strong correlations between linc00152 and the diagnosis, prognosis, and metastasis of cancers, particularly lymph node metastases . A recent meta‐analysis of the data for 913 cancer patients further confirmed the diagnostic utility of linc00152 as well as its association with lymph node metastases, advances in the TNM stage, and shorter overall survival .…”
Section: Clinical Application Of Linc00152 In Cancersmentioning
confidence: 93%
“…We also detected significant downregulation of MIR155HG, whose high expression is associated with glioma progression and poor survival [52]. Another downregulated lncRNA with relevance to prognosis is linc000152, whose increased expression has been observed in multiple tumor types [53,53]. On the other hand, we observed a significant upregulation of two "oncogenic" lncRNAs, NEAT1 and FTX.…”
Section: Resultsmentioning
confidence: 54%